1992
DOI: 10.3402/tellusb.v44i2.15429
|View full text |Cite
|
Sign up to set email alerts
|

Northern fens: methane flux and climatic change

Abstract: Methane flux from northern peatlands is believed to be an important contribution to the global methane budget. High latitude regions are predicted to experience significant changes in surface temperature and precipitation associated with the 2 x C0 2 climate scenarios, but the effects of these changes on methane emission are poorly understood. A peatland hydrologic model predicted June-August decreases in water storage of between 82 and 144 mm, using as inputs increases in temperatures of 3 °C and rainfall of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
58
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(68 citation statements)
references
References 32 publications
9
58
0
Order By: Relevance
“…Another study showed a comparable increase in high latitude emissions in response to warming, but a large reduction should the water table drop [Roulet et al, 1992]. That model's results appear comparable to ours, since our simulations showed increased precipitation at high latitudes along with warmer temperature and therefore an increased emission.…”
Section: Resultssupporting
confidence: 78%
“…Another study showed a comparable increase in high latitude emissions in response to warming, but a large reduction should the water table drop [Roulet et al, 1992]. That model's results appear comparable to ours, since our simulations showed increased precipitation at high latitudes along with warmer temperature and therefore an increased emission.…”
Section: Resultssupporting
confidence: 78%
“…Changes in temperature and precipitation and the associated effects on water table position will influence methanogenesis and CH 4 emission in a predictable manner (Roulett et al, 1992;Moore, 1994). However, climate changes will also affect plant production and seasonality as well as the area of distribution of P. australis (Matthews, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to changes in land use practices, warming and increased evapotranspiration associated with climate change will lead to drying of peatlands unless increases in precipitation alleviate soil moisture deficits 16,17 . Whereas projected annual water yields in North American basins vary by region and by global or regional climate model scenarios, higher evapotranspiration from warming generally is expected to compensate for increases in precipitation in some regions and will magnify the effects of precipitation declines in other regions 18,19 .…”
mentioning
confidence: 99%